IS Misconception of Bay’at: Nuances in Oath of Allegiance - Muhammad Saiful Alam Shah Bin Sudiman (2017)
Investigations of a Singaporean national Imran Kassim on terrorism-related charges reveal that a flawed understanding of the concept of bay’at (oath of allegiance) played a role in his violent radicalisation. It is vital to advance a nuanced understanding of the concept to prevent people from falling prey to extremists’ narrative and exploitation of concepts like bay’at.